2018
DOI: 10.1093/cid/ciy796
|View full text |Cite
|
Sign up to set email alerts
|

Increased Relative Abundance of Klebsiella pneumoniae Carbapenemase-producing Klebsiella pneumoniae Within the Gut Microbiota Is Associated With Risk of Bloodstream Infection in Long-term Acute Care Hospital Patients

Abstract: In adult LTACH patients, carbapenem receipt was associated with increased hazard for high relative abundance of KPC-Kp in the gut microbiota. Increased relative abundance of KPC-Kp was associated with KPC-Kp bacteremia. Whether bacteremia arose directly from bacterial translocation or indirectly from skin contamination followed by bloodstream invasion remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 32 publications
4
79
0
2
Order By: Relevance
“…In prospective studies, these procedures are time consuming and can not be applied in numerous labs. Quantitative studies with other bacteria are very rare, based on total microbiota analyses or absent and these studies are needed (11, 12). To have the opportunity to freeze directly available devices could be useful in many labs and increase the feasibility of these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In prospective studies, these procedures are time consuming and can not be applied in numerous labs. Quantitative studies with other bacteria are very rare, based on total microbiota analyses or absent and these studies are needed (11, 12). To have the opportunity to freeze directly available devices could be useful in many labs and increase the feasibility of these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have identified CRE colonization as a risk factor for subsequent CRE infection (6,7), available investigations do not explore whether this risk differs based on the production of carbapenemases by the colonizing strain. This information is important because it can guide whether the additional step of performing phenotypic or genotypic testing on rectal isolates positive for CRE provides added value.…”
mentioning
confidence: 99%
“…Therefore, decreasing the intestinal loads of OXA-PE might be an effective way to reduce the risk of cross-transmission in wards harboring colonized patients. Moreover, the decrease of the OXA-PE loads below the detection limits can also reduce the risk of developing an infections during hospitalization [20][21][22]. This could be useful in situations where programmed surgical procedures are to be performed and for managing critically ill patients, especially since the decrease of the OXA-PE loads after the onset of treatment was fast and maintained throughout the treatment.…”
Section: Discussionmentioning
confidence: 99%